Antimicrobial and Bacteriological Study for Men Patients with Respiratory Disorder Diseases - Hasanain Khaleel Shareef (Journal of Global Pharma Technology, 2018)
The current study aimed to designation and investigation for bacteria in the respiratory secretions 40 sputum samples form men patients which found after laboratory examination 40 samples infected with pathogenic bacteria in respiratory disorder diseases patients infected with lung cancer and pneumonia , the results included of Gram Positive Bacteria isolated were: Staphylococcus epidermidis had the most presence with 24 (60%) , followed by Streptococcus pyogenes with 5 (12. 5%) , followed by 3(7. 5%) for Staphylococcus aureus ,and about Streptococcus pneumonia represented the lowest percentage 2(2.5%) ,while the Gram Negative Bacteria isolated from sputum were : Klebsiella spp. and Escherichia coli have the same percentage had the equal presence with2(5% ),while Mycobacterium tuberculosis with 2(5% ),also the study had been included the determination of the antibiotic effected of ( Key: AMC=Augmenting/Amoxicillin, E=Erythromycin, CIP=Ciprofloxacin, AZM= Azithromycin ,CN=Gentamycin, CRO=Ceftriaxone, AM=Ampicillin , P=Penicillin ) on bacterial pathogen isolates from respiratory disorder diseases, they were found: resistance to Azithromycin, Augmenting/Amoxicillin, Ciprofloxacin, Ampicillin and Penicillin were showed by most for bacteria, while most isolated have been found to be sensitive to Gentamycin with Ceftriaxone. Mycobacterium tuberculosis and Streptococcus pneumoniae species showed resistance to most of antibiotics, Kellbesilla spp. showed resistance to most of antibiotic agents except Ceftriaxone while Streptococcus pyogenes which isolates displayed sensitive for most antibiotics except for Augmenting/Amoxicillin, Ampicillin and Penicillin. Generality of the isolates were Escherichia coli showed best sensitivity to Gentamycin just but resistance for all antibiotics in the study, Staphylococcus epidermidis had to be sensitive for Augmenting/Amoxicillin, Gentamycin and Ceftriaxone which Staphylococcus aureus had to be sensitive for antibiotics agents Gentamycin and ceftriaxone. Conclusions: The respiratory disorder diseases are a serious problem and healthy issue in any community that might refer to elevation diseases of males than females. Also the most common bacteria accompanying in (Lung cancer, pneumonia) are Staphylococcus epidermidis, Streptococcus pyogenes and Staphylococcus aureus respectively from patients in Babylon province. Although the proper antibiotics had been used were the Gentamycin and Ceftriaxone which give high sensitivity for studied bacterial species.Keywords: Respiratory; Disorder; Diseases; Lung; Cancer; Pneumonia; Respiratory; Allergic; Antibiotic.